Calibration of on-chip cell electroporation by a pseudo-volumetric uptake model. (August 2017) - Kim, Kisoo; Lee, Won Gu
Highlights: The calibration of on-chip electroporative uptake intensity by using the pseudo- volumetric model was presented. A quantitatively calibrated calculation of the amount of uptake intensity and its relative ratio in electroporation was suggested. The underlying uptake phenomena of on-chip cell electroporation can be visualized and estimated in a more accurate and quantitative manner. Abstract: Most conventional methods for assessing uptake of exogenous molecules and nanomaterials into cells use the projected two-dimensional (2D) area of uptake intensity into individual cells. However, since most cells have a three-dimensional (3D) spherical shape, volumetric uptake cannot be quantified accurately using 2D area analysis. Here, we present a method for calibrating the electroporative uptake intensity of small molecules by using a novel predictable spherical volume (PSV) model, which is more accurate and quantitative than previous methods. As a proof-of-concept, we visualized the electroporative uptake of propidium iodide (PI) into mammalian cells in a single rectangular polydimethylsiloxane (PDMS) microfluidic channel, often used for direct observation of on-chip cell electroporation. Our PSV method yielded more accurate results than conventional methods and faithfully reflected volumetric changes in uptake intensity, even those due to microflow. We believe that this approach can be potentially beneficial for screening the electroporative uptake efficiency of cell-membrane impermeable nanodrugs, such as functional nanoparticles incorporated with a small drug capable of slowly diffusing inside cells.